Manubu and Ganu - Bonifacio, Bob O.; Daves, Manuel C.; De Leon, Noel T. (Manila Communication Foundation for Asia)
A parable about life today, it is the sensitive discovery of life's meaning by a little boy which contains insights into such problems as industrialization pollution, progress and poverty.
Based on the book, Hanubu & Ganu by Bob O. Bonifacio.
Keywords: Pollution -- Philippines; Poverty